1998
DOI: 10.1046/j.1365-2249.1998.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioids modulate allograft rejection time in mice: possible relation with Th1/Th2 cytokines

Abstract: SUMMARYThe continuous infusion of the opioid peptide b-endorphin prolongs skin allograft survival in mice, while the opiate receptor antagonist naloxone, administered together with the opioid at the time of transplantation, abolishes the effect of the opioid. Consistently, naloxone, when given alone at the time of transplantation, but not later, accelerates graft rejection and increases splenocyte IL-2 and interferongamma (IFN-g) production. Splenocyte b-endorphin concentrations are lower in transplanted anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…As a consequence of these regulatory circuits, -opioid receptors are preferentially expressed in type 2 but not type 1 T helper cells . Moreover, exogenous and endogenous -opioid ligands skew the T helper cell balance into the direction of type 2 T helper cells (Sacerdote et al, 1998(Sacerdote et al, , 2000Roy et al, 2001Roy et al, , 2004. It is interesting that the transcription of -opioid receptors in response to IL-4 is mediated by the transcription factors STAT6 and GATA3, which is typical for several genes expressed in type 2 T helper cells (Kraus et al, 2001;Börner et al, 2004b.…”
Section: Activation Of T Lymphocytes Induces -Opioid Receptors 501mentioning
confidence: 99%
“…As a consequence of these regulatory circuits, -opioid receptors are preferentially expressed in type 2 but not type 1 T helper cells . Moreover, exogenous and endogenous -opioid ligands skew the T helper cell balance into the direction of type 2 T helper cells (Sacerdote et al, 1998(Sacerdote et al, , 2000Roy et al, 2001Roy et al, , 2004. It is interesting that the transcription of -opioid receptors in response to IL-4 is mediated by the transcription factors STAT6 and GATA3, which is typical for several genes expressed in type 2 T helper cells (Kraus et al, 2001;Börner et al, 2004b.…”
Section: Activation Of T Lymphocytes Induces -Opioid Receptors 501mentioning
confidence: 99%
“…The opioid receptor antagonist naloxone has been shown to enhance Th1-mediated responses, including skin graft rejection, in a murine model (12). In these studies, naloxone increased the production of IL-2 and IFN-␥ by splenocytes to promote rejection, indicating that endogenous ␤-endorphin normally inhibits IFN-␥ production.…”
mentioning
confidence: 90%
“…Previous studies (Sacerdote in 1998 and revealed that naloxone as an opioid antagonist is able to trigger the immune response to the Th1 pattern, and is also able to strengthen immune responses after vaccination (24,25). Jamali et al observed that naloxone can increase the levels of IFN-γ cytokine and cellular immune responses against herpes simplex virus infection, and hypothesized the possibility of adjuvant effect of naloxone on HSV-I vaccine (27).…”
Section: Hbs-nlx10mentioning
confidence: 99%
“…During the last decade, many studies have used this agent as adjuvant in the formulation of different vaccines. They showed that naloxone can induce TH1 pattern of immunity and increase the IFN-γ level (14,16,22,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%